Impact of resistance and endurance exercise training on femoral artery function: sex differences in humans - Green, Daniel J.; Thomas, Hannah J.; Marsh, Channa E.; Lester, Leanne; Naylor, Louise H.; Haynes, Andrew (The Journal of physiology, 2025)
Exercise has direct and indirect anti‐atherogenic impacts on arterial function and health in humans. Few studies have directly compared the impacts of different commonly adopted exercise approaches on femoral artery function. We hypothesized that, owing to its direct impact via sustained increases in shear stress, endurance (END) training would have larger impacts on arterial diameter and function than resistance (RES) training. Thirty‐nine young, healthy participants (age 26.9 ± 6.2 years, 22♀) completed 12 weeks of both RES and END training in random order, separated by a 12 week washout. Resting femoral artery diameter and flow‐mediated dilatation (FMD) were collected before and after each exercise intervention. END training was associated with an increase in both FMD (Δ1.61 ± 3.09%, P = 0.005) and resting diameter (Δ0.15 ± 0.29 mm, P = 0.004). Neither resting diameter nor FMD increased following RES. However, sex difference analysis revealed that males increased FMD following RES (Δ2.21 ± 3.76%, P = 0.015), whereas no RES change was evident for females. Following END, both males and females increased FMD (♂, Δ1.11 ± 1.65%; ♀, Δ1.88 ± 3.67%; both P = 0.025), with males also showing an increase in resting arterial diameter following END (Δ0.23 ± 0.2 mm, P < 0.001). Group data revealed that END has greater impacts than RES on femoral artery diameter and flow‐mediated functional responses, which are endothelium mediated and nitric oxide dependent. Males exhibit beneficial impacts in response to both END and RES, whereas females respond predominantly to END. Our findings suggest that arterial adaptation to exercise might be influenced by exercise modality and sex. Key points Exercise has anti‐atherogenic effects and lowers the risk of cardiovascular diseases. This is mediated, in part, by the direct haemodynamic impacts of exercise on arterial function, structure and health. Different modalities of exercise have distinct effects on arterial haemodynamics, but few studies have directly compared, within subjects and using a cross‐over design of trial, the relative impacts of distinct forms of exercise training on arterial adaptation. In this study, endurance training increased baseline femoral artery diameter and flow‐mediated dilatation, which is endothelium dependent and mediated by nitric oxide. Resistance training had a beneficial but lesser impact. Females and males were responsive to endurance training, but only males responded positively to resistance training in this study. These results show that changing the training mode modifies training‐induced arterial adaptation; this has implications for the optimization of exercise prescription for individual benefit. figure legend This randomized cross‐over study addressed the hypothesis that endurance training would have larger impacts on arterial diameter and function than resistance training. Endurance training increased flow‐mediated dilatation (FMD) and resting diameter, whereas resistance training did not modify either. However, sex differences were apparent. Males exhibited beneficial impacts in response to both endurance and resistance training, whereas females responded predominantly to endurance training. Our findings suggest that arterial adaptation to exercise might be influenced by exercise modality and sex.